Expression of apoptosis related genes in buffalo embryos produced through in vitro fertilization and parthenogenetic activation - SINGH, M K; SAW, S; SINGH, K P; SAINI, N; KAUSHIK, R; MANIK, R S; PALTA, P; SINGLA, S K; CHAUHAN, M S (The Indian Journal of Animal Sciences, 2014)
In present study immature oocytes were obtained from buffalo slaughterhouse ovaries and were subjected to in vitro maturation (IVM) in TCM-199 + 10% FBS + 5 µg/ml pFSH + 0.81 mM sodium pyruvate + 5% buffalo follicular fluid for 24 h in a CO2 incubator (5% CO2, 90–95% relative humidity) at 38.5°C. The maturer oocytes were used for IVF and the cleaved embryos were cultured for 8 days, while the parthenotes were produced with exposure of 7% ethanol, 6- dimethyl aminopurine and cultured for 8 days in mCR2aa medium. The relative abundance of BCL-XL transcripts in immature, matured oocytes; and embryos produced through IVF i.e. 2-cell, 4-cell, 8-16-cell, morula and blastocyst stage were 25.33±0.90, 12.67±1.20, 37.67±0.90, 30.67±0.30, 23.67±0.90, 18.33±0.90 and 27.00±1.20 respectively, while in parthenogenesis these values were 23.67±0.88, 13.67±1.20, 23.67±1.20, 22.34±0.88, 24.34±0.88, 33.67±0.88, 45.34±1.20 respectively. Relative abundance of BAX transcripts by IVF were 23.0±0.60, 0.33±0.10, 4.00±0.60, 5.00±0.60, 0.37±0.06, 13.0±0.66 and 56.7±0.90; and by parthenonenesis were 22.3±0.90, 0.13±0.03, 13.67±0.90, 14.0±0.60, 15.33±0.90, 64.67±2.20 and 55.0±2.10 respectively. In conclusion, expression pattern of apoptosis related genes revealed that incidence of apoptosis was significantly higher in IVF and parthenogenetically produced buffalo embryos at stages like immature oocytes, morula and blastocyst stage than the early cleavage stage embryos.